161k views
1 vote
What is the solution of equation for -3x^3 -x^2 + 54x -40 = 2x^2 + 6X + 20

User Wintour
by
6.0k points

1 Answer

4 votes

Answer:

The solved given equation is
x^3+x^2+16x-20=(x-2)(x-2)(x+5).

Explanation:

Given equation is
-3x^3-x^2+54x-40=2x^2+6x+20

To solve the given equation:


-3x^3-x^2+54x-40-2x^2-6x-20=0


-3x^3-3x^2+48x-60=0

Multiply the above equation into
-(1)/(3) on both sides


-3x^3-3x^2+48x-60* (-(1)/(3))=0* (-(1)/(3))


x^3+x^2+16x-20=0

To sove the equation by using synthetic division method

2_| 1 1 -16 20

0 2 6 -20

___________

1 3 -10 0

Therefore x-2 is a factor

Therefore the quadratic equation is
x^2+3x-10=0

(x-2)(x+5)=0

(x-2)=0 or (x+5)=0


x^2+3x-10=(x-2)(x+5)

Therefore the factors are x-2,x-2,x+5

Therefore the solved given equation is
x^3+x^2+16x-20=(x-2)(x-2)(x+5)